PERAN MEDIASI ORIENTASI KEWIRAUSAHAAN PADA ORIENTASI PASAR DAN INOVASI PRODUK TERHADAP KINERJA PEMASARAN PADA UMKM MAKASSAR TRADE CENTER KAREBOSI - Wahyu Wahyu; Rahayu Lestari (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aimed to examine the mediating role of entrepreneurial orientation on market orientation and product innovation on marketing performance. The population of this research is 200 MSME electronic shops in Makassar Trade Center. The sampling technique in this study used purposive sampling, the number of samples used was 150 people. The analytical tool used is the Structural Equation Model (SEM) through AMOS Version 22 software. The results show that there is an influence between market orientation on entrepreneurial orientation, product innovation on entrepreneurial orientation, market orientation on marketing performance, and product innovation on marketing performance. While Entrepreneurial Orientation can mediate market orientation on marketing performance and Entrepreneurial Orientation can mediate product innovation on marketing performance.